Does fruit cooling and seed film coating affect the germination potential of physalis? - Campos, Aniela (2015)
Physalis (Physalis peruviana L.) is a native fruit of the Andes widely accepted in the national and international market. The berries have high commercial value, being very nutritious and tasty. Physalis cultivation in Brazil is currently expanding mainly southwards. Seeds carry out propagation. However, information concerning factors that could affect germination viability are scarce. Thus, the goal of this study was to assess the effects of storage and of film coating on the germination potential of physalis seeds. The experimental design was completely randomized in a 2x3 factorial, considering two fruit storage conditions (environment and cooling) x and three coating polymers to film-coat the seeds (Blue AG L-204® DISCO, Red AG L-203®DISCO, water), with five replications and one hundred seeds per plot. Germination was evaluated seven, 14 and 21 days after sowing to calculate the germination rate index. The physalis fruit cold storage for seven days does not affect the germination viability of the seeds. Seed coating increases the germination percentage and speed.